Serviços tecnológicos e atividades inovativas no sistema de inovação de Sorocaba/SP - Pakes, Paulo Renato (2015)
To compete globally, companies need to build and accumulate technological capabilities for operation activities and innovation activities. Despite the development of technological capability to innovate primarily take place within companies, other organizations in the innovation system may contribute to this process. In this sense, this study aimed to characterize the industrial innovation activities on a Local Innovation System (LIS) and analyze its fragmentation. The local innovation system of Sorocaba / SP was defined as an object of study. An integrated unique case study was conducted, the sample was composed of 43 companies from various sectors. It has been described the level of knowledge of the companies in relation to innovation legislation, the intention of investments in related technologies to market, management and production, the structure of Research and Development (R&D) and innovation management, relevant factors to the practice of innovation , partnerships for innovation, as well as the demand for technological services in Basic Industrial Technology. In addition, Data collected included the supply of technological services from 19 institutions of science, technology and innovation leading to a comparative analysis in relation to the services demanded by the local industry. Among the results, it was found: a) lack of knowledge about the innovation law; b) the intention of investments in technologies focuses on the areas of production and management c) about half of the companies has innovation management department or R & D department structured; d) interaction with STI public and private institutions has little relevance to the practice of innovation; e) the formation of partnerships to innovate occurs mainly with customers and suppliers; f) the interaction among industries and other institutions from the LIS suggests that the observed level of local interaction is reduced, so that the LIS appears as fragmented.